2014
DOI: 10.3892/or.2014.3172
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of DNA-binding protein 1 knockdown arrests the growth of colorectal cancer cells and suppresses hepatic metastasis in vivo

Abstract: Abstract. Inhibitor of DNA-binding protein 1 (ID1) is commonly abnormally overexpressed in colorectal cancer (CRC); yet, the functional significance of ID1 in the growth and invasive properties of CRC cells remains largely unclear. The present study investigated the effects of ID1 downregulation on the cell growth and metastatic features of CRC. Using lentiviral shRNA infection, stable ID1-knockdown (KD) HCT116 and SW620 cells, human metastatic CRC cell lines, were created. In vitro, the migration/invasion cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…ID1 is an inhibitor of DNA binding that interacts and inhibits the transcriptional activation ability of basic HLH proteins which leads to tumour growth and angiogenesis [45]. Knockdown of ID1 has been shown to significantly decrease mRNA and protein levels of survivin in colorectal cancer cells [46] as well as to remove survivin inhibition of apoptosis in head and neck squamous cell carcinoma [47]. BIRC5 encodes the expression of anti-apoptotic protein survivin and elevated activity of this survival cascade has been implicated in cancer cell survival and disease progression [48,49,50].…”
Section: Resultsmentioning
confidence: 99%
“…ID1 is an inhibitor of DNA binding that interacts and inhibits the transcriptional activation ability of basic HLH proteins which leads to tumour growth and angiogenesis [45]. Knockdown of ID1 has been shown to significantly decrease mRNA and protein levels of survivin in colorectal cancer cells [46] as well as to remove survivin inhibition of apoptosis in head and neck squamous cell carcinoma [47]. BIRC5 encodes the expression of anti-apoptotic protein survivin and elevated activity of this survival cascade has been implicated in cancer cell survival and disease progression [48,49,50].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have highlighted the complex role served by members of the ID subfamily in mammalian cell fate determination (21,27,28,34). IDs are involved in numerous biological processes, including the inhibition of differentiation, and the maintenance of self-renewal and multipotency in stem cells (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [18] found that ectopic expression of Id-1 could regulate the cell cycle, promote cell proliferation and metastasis, while down-regulation of Id-1 expression had the opposite effect. Lai et al [19] used RNAi technology to knock down Id-1 expression in colorectal cancer cells. It was found that the cell proliferation ability decreased, the number of migration and invasion cells decreased significantly, and the expression of matrix metalloproteinase-2 decreased.…”
Section: Discussionmentioning
confidence: 99%